PELAKSANAAN KEBIJAKAN PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) - Lesmana, Romy (Jurnal Ilmu Administrasi Negara, 2016)
Implementation of the District Integrated Administrative Service Policy (Patent). The purpose of this study was to determine and analyze the implementation of the policy of integrated administrative services (PATENT) in District Tualang Siak and a limiting factor in implementation. This study belongs to the type of qualitative research, The informants in this study is the district head, sekcam, patent officers and community service recipient patents. Data collection techniques, are: obsrvasi, interviews and documentation. Data were analyzed using an interactive model. The results showed that the implementation of policies in the district PATENT tramp services Siak has been quite good, although still found problems in the availability of field personnel are limited in quantity and quality.